2021
DOI: 10.11648/j.ijepp.20210903.11
|View full text |Cite
|
Sign up to set email alerts
|

Public Urban Green Spaces’ Visiting Habits and Perception Regarding Their Health Benefits in Addis Ababa City, Ethiopia

Abstract: Physical structure and activities undertaken at green spaces provide substantial health, social, environmental, psychological, and economic benefits to residents of an urban area. Study regarding the health benefits of green spaces in developing countries is very limited. Addis Ababa is the capital and the largest city in Ethiopia and not many studies on green spaces are available. Thus, this community-based cross-sectional study was conducted among 204 residents of Addis Ababa city. A multistage sampling tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…The strongest predictor of the willingness of the young people to use the green spaces was their perception of the accessibility of such spaces. A study conducted by Beyene and Borishe (2021) in Addis Ababa showed that perceptions of health benefits have a significant association with the visiting habits of people to green spaces. People who held positive perceptions of the health benefits offered by UGSs were two times more likely to visit green spaces than the people who held negative perceptions.…”
Section: Ugss and Improved Health Well-being And Quality Of Lifementioning
confidence: 99%
See 4 more Smart Citations
“…The strongest predictor of the willingness of the young people to use the green spaces was their perception of the accessibility of such spaces. A study conducted by Beyene and Borishe (2021) in Addis Ababa showed that perceptions of health benefits have a significant association with the visiting habits of people to green spaces. People who held positive perceptions of the health benefits offered by UGSs were two times more likely to visit green spaces than the people who held negative perceptions.…”
Section: Ugss and Improved Health Well-being And Quality Of Lifementioning
confidence: 99%
“…It was further observed in the literature review that the presence of green space directly impacts the human mind psychologically. Urban park users visit parks for fresh air, to relieve stress, and to relax (Sreetheran, 2017;Beyene and Borishe, 2021) and for social interaction (Nasir and Rahim, 2020). Highlighting walking and talking as the most common activities enjoyed in parks of southwest Spain, Gozalo et al (2019) observed that the absence of noise and the air quality in green spaces contributed to the relaxation the users felt in both small and large green spaces.…”
Section: Ugss As Places For Recreation and Stress Reductionmentioning
confidence: 99%
See 3 more Smart Citations